Development of Self-Checkout In A Shop with Fraud Detection by Using Weight Comparison - Abdul Razak, Mohamad Aidil Firdaus; Tee, Kian Sek (Evolution in Electrical and Electronic Engineering, 2022)
The development of self-checkout in a shop with fraud detection by using weight comparison was introduced which to ensure the GDP is less affected according to COVID-19 and minimize standard operation procedures to avoid fraudulent activity who used the self-checkout. The main objective was to develop an auto payment machine with weight comparison as fraud detection and the scope of the study was to design the practical tools by using the exact hardware for conventional usage. The method of development had three parts electronic and electrical design, mechanical design and software design. The entire body conveyor was built 44.8cm long, 23.3cm in width and 28.3cm in height with the electronic attachment that control by the microcontroller, Arduino Uno and NodeMCU to serial communication with the transaction shown on the website. Throughout the development process, the main objective had been successfully achieved and a recommendation for future work was weight comparison can detect even the multiple scan barcode groceries on the conveyor with an indicator to detect fraudulent activities.